Theoretical Study of Electrical Properties of a Germanium and Gallium Arsenide P-N Junction Diode in an Open Circuit - Bello Adekunle Kazeem (Darul Yasin Al Sys, 2025)
Theoretical study of electrical properties of a Germanium and Gallium arsenide p-n junction diode in an open circuit is investigated using one dimensional Poisson equation. It is assumed that the conduction electrons and holes obey Boltzmann equation of statistical mechanics. The comparison of electrical properties variation within the p-n junction for the two semi-conductor materials is describe and discussed. There is high intrinsic concentration in elemental semiconductor , while the bond existing in doped semiconductor results in lesser value. The corresponding electron and hole concentrations, the temperature values are within (200 – 500) K. The curves for a plane p-n junction in germanium and gallium arsenide are presented in figures 2 and 3.